Dampak Covid-19 Terhadap Pendapatan Pedagang Kecil Bidang Kuliner Di Cikarang Utara, Kab. Bekasi pada Era New Normal - Kristi Indriyani; Jonathan Lampatar Siregar; Dimaz Ramananda (Politeknik Negeri Ambon, 2023)
Small traders are one of the informal sectors that are an alternative for those who do not have special rules that require them to work. This study aims to determine and also to analyze the income of small traders, especially in the culinary field during the New Normal period located in Karangasih Village, North Cikarang District, Bekasi Regency. The research method used is using a qualitative method with a descriptive analysis approach. The data collection tools used interviews and observations. There are as many as 35 population samples taken in this study, namely from small traders in the culinary field in Sugih Waras Village as many as 35 people. Based on the analysis and discussion of the results of interviews with informants regarding the impact of the New Normal Era on the income of small traders in the culinary field. So it can be concluded that the New Normal Era has a positive impact, increasing the income of small traders, especially in the culinary field. It is proven by all the research populations experiencing an increase in income from the pandemic era to the new normal era.